Charged particle dynamics in multiple colliding electromagnetic waves. Survey of random walk, Lévy flights, limit circles, attractors and structurally determinate patterns. (9th March 2017) - Bulanov, S. V.; Esirkepov, T. Zh.; Koga, J. K.; Bulanov, S. S.; Gong, Z.; Yan, X. Q.; Kando, M.
Abstract : The multiple colliding laser pulse concept formulated by Bulanov et al. ( Phys. Rev. Lett ., vol. 104, 2010 b, 220404) is beneficial for achieving an extremely high amplitude of coherent electromagnetic field. Since the topology of electric and magnetic fields of multiple colliding laser pulses oscillating in time is far from trivial and the radiation friction effects are significant in the high field limit, the dynamics of charged particles interacting with the multiple colliding laser pulses demonstrates remarkable features corresponding to random walk trajectories, limit circles, attractors, regular patterns and Lévy flights. Under extremely high intensity conditions the nonlinear dissipation mechanism stabilizes the particle motion resulting in the charged particle trajectory being located within narrow regions and in the occurrence of a new class of regular patterns made by the particle ensembles.